Análise socioeconômica na perspectiva dos gestores e cooperados em uma cooperativa agropecuária da região central do RS - Wakulicz, Gilmar Jorge (2023)
Cooperatives are entities that have a dual function, econoic and social, na unlike commercial companies, members are both owners and users of the enterprise. These aspects highlight the need to evaluate cooperatives differently from other capitalist companies, taking care not to forget their social purpose. The general objective of this study is to understand how the economic and social nature/function is perceived by the cooperative members and managers and if there is a balance between the interests of the organization and the cooperative members, mainly regarding the social aspect in na agricultural cooperative. The specific objectives are, to analyze the socioeconomic performance in a cooperative of the agricultural branch; demonstrate the perception of managers of an agricultural cooperative in relation to its social and economic function; understand the perceptions of cooperative members regarding the economics and social aspects of a cooperative organization in the agricultural sector; and, understand how the cooperative members and technicians of the cooperative perceive the Technical Assistance and Rural Extension services provided by the Technical Department. As a methodological procedure, the case study strategy was used. Data collection covered complete balance sheets for the years 2016 to 2022 as well as cooperative management report, direct observation and semi-structured interviews with four managers and three members of the Technical Departament, applicaton of a survey (68 questionnaires with quantitative and qualitative data). Descriptive statistics, content analysis technique, SPSS 23.0® software and discourse analysis were used for data analysis. From the analysis of the economic-financial indicators, it is observed that the cooperative presents sensitive indicators – increase in the total debt level over the years and the significant dependence on third-party capital for investiments in the short and long term, in relation to equity liquid. With regard to social indicators, the social capital indicator paid in by the cooperative stands out, due to the decision to annually return part of the share of the associates, a policy that can compromise the financial health of the cooperative, because by reducing the social capital the cooperative will need to raise financial resources from third parties, probably with higher interest rates. In the perception of the managers, there is the fulfilment of the economic and social functions in the cooperative. However, for managers and cooperative members, the social function is closely linked to tehnical assistence. In the economic function, the main link between the cooeprative and the members is the price paid to the producer for is deposited crop. The cooperative members understand that the cooperative does not meet all their needs. It is concluded that managers should pay attention to the inidcators that show negative growth, such as the level of indebtedness, so that in the médium and long term it remains financially healthy. The cooperative members, despite claiming to know the dual economic and social function of a cooeperative, have difficulty defining the variables that represent them. Also, it is possible to state that the non-contemplation of somo of the wishes of the cooperative members can come from the low presence in the forums of representation of the associates, where they can discuss what are their interests together with the managers of the organization.